An Improved Catalyst for Iodine(I/III)‐Catalysed Intermolecular CH Amination. Issue 13 (31st March 2016) - Lucchetti, Nicola; Scalone, Michelangelo; Fantasia, Serena; Muñiz, Kilian
Abstract: 1, 2‐Diiodobenzene is presented as an efficient catalyst precursor for the intermolecular amination of arenes under homogeneous conditions. N ‐Troc‐ and N ‐phthalimido‐substituted methoxyamines serve as suitable nitrogen sources providing the corresponding aniline derivatives in up to 99% yield and with up to 66:1 regioselectivity. Key for this successful CN coupling protocol is the strained μ‐oxo‐bridged conformation of the bisiodine(III) catalyst, which induces unparalleled high reactivity. Abstract :